SEROLOGICAL ANTIBODY RESPONSE OF THE CLASSES IgM AND IgG ANTI-Toxoplasma gondii IN DOGS WITH OCULAR ALTERATIONS - Rodrigues, Nássarah Jabur Lot [UNESP]; Manzini, Suzane [UNESP]; Oliveira, Natalie Newirt [UNESP]; e Gava, Mariana Zanchetta [UNESP]; Gonçalves, Lenise Garbelotti [UNESP]; Hirota, Inajara Nakaruma [UNESP]; Ferreira, Annalu Pinton [UNESP]; De Sessa, Mariana [UNESP]; Ferreira, Mayara Chagas [UNESP]; Reiter, Luis Felipe Fernandes [UNESP]; Brandão, Claudia Valeria Seullner [UNESP]; Langoni, Helio [UNESP]; et al. (Universidade Federal do Paraná, 2021)
Toxoplasmosis is a worldwide distribution zoonosis, caused by the protozoan Toxoplasma gondii (T. gondii). In dogs, ocular toxoplasmosis is considered rare and lesions include keratoconjunctivitis sicca, uveitis, iridocyclitis, ciliary epithelial hyperplasia, retinitis, choroiditis, extraocular myositis, scleritis, episcleritis, optic neuritis, and corneal and conjunctival masses. Thus, the present study aimed to detect IgM and IgG class antibodies against T. gondii in 75 dogs with ophthalmic signs, treated at the Veterinary Hospital of FMVZ Unesp, Botucatu city. Serological results for the detection of IgM and IgG class antibodies were evaluated by the Indirect Immunofluorescence Reaction (RIFI) technique associated with data from a questionnaire regarding the risk factors for toxoplasmosis in the canine species administered to the animal’s guardian on the day of blood collection, regarding the risk factors for toxoplasmosis in canine species. The results were 28/75 (37%) for IgG class antibodies and 34/75 (45%) for IgM class, that is, 37% of the animals were exposed to a pre-infection and 45% were in the acute phase of the disease. 65% of dogs had uveitis as a clinical sign; the others had keratoconjunctiva, ulcers, conjunctivitis, retinochoroiditis, iridocyclitis, retinitis and choroiditis. The importance of observing the ocular changes in patients was noted because it may suggest the presence of an infectious disease.
Resposta sorológica das classes IgM e IgG anti-Toxoplasma gondii em cães com alterações oculares
Keywords: alterações oculares; cão; dog; eye diseases; Toxoplasma gondii